2019
DOI: 10.3390/ijms20235935
|View full text |Cite
|
Sign up to set email alerts
|

Endomorphin-2- and Neurotensin- Based Chimeric Peptide Attenuates Airway Inflammation in Mouse Model of Nonallergic Asthma

Abstract: We examined anti-inflammatory potency of hybrid peptide-PK20, composed of neurotensin (NT) and endomorphin-2 (EM-2) pharmacophores in a murine model of non-atopic asthma induced by skin sensitization with 2,4-dinitrofluorobenzene and intratracheal challenge of cognate hapten. Mice received intraperitoneally PK20, equimolar mixture of its structural elements (MIX), dexamethasone (DEX), or NaCl. Twenty-four hours following hapten challenge, the measurements of airway responsiveness to methacholine were taken. Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 78 publications
1
7
2
Order By: Relevance
“…Apart from airway hyperreactivity, another feature of asthma is the airway inflammation described by the influx of inflammatory cells into the airways and the levels of inflammatory cytokines in both the lung tissue and BALF. The total number of inflammatory cells in sensitized, non-inhaled animals in our study was about three to ten times higher than in previous reports [42,43], which is probably in relation to the repeated hapten challenge. Moreover, we obtained a comparably elevated level of neutrophils, together with a lack of eosinophils, as it was observed previously [42,43].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Apart from airway hyperreactivity, another feature of asthma is the airway inflammation described by the influx of inflammatory cells into the airways and the levels of inflammatory cytokines in both the lung tissue and BALF. The total number of inflammatory cells in sensitized, non-inhaled animals in our study was about three to ten times higher than in previous reports [42,43], which is probably in relation to the repeated hapten challenge. Moreover, we obtained a comparably elevated level of neutrophils, together with a lack of eosinophils, as it was observed previously [42,43].…”
Section: Discussioncontrasting
confidence: 80%
“…The total number of inflammatory cells in sensitized, non-inhaled animals in our study was about three to ten times higher than in previous reports [42,43], which is probably in relation to the repeated hapten challenge. Moreover, we obtained a comparably elevated level of neutrophils, together with a lack of eosinophils, as it was observed previously [42,43]. Neutrophilia and the absence of eosinophils are key features of non-atopic asthma [44], both in humans and in animal models [45], which may determine the cytokine spectrum in blood, BALF, and lung tissue [1].…”
Section: Discussioncontrasting
confidence: 80%
“…Our latest report confirmed that the chimera alleviated inflammatory symptoms in the murine model of nonallergic asthma induced by sensitization with 1‐fluoro‐2,4‐dinitrobenzene (DNFB); a low molecular weight compound 16 . In fact, it has been proven that PK20 reduced influx of inflammatory cells into bronchoalveolar lavage fluid (BALF) and lungs, limited expression of nuclear transcription factor NF‐κB and concentration of pro‐inflammatory cytokines, malondialdehyde (MDA), secretory phospholipase A 2 (sPLA 2 ) and mouse mast cell protease (MCPT 1) in lung tissue, as well as the level of albumin in BALF.…”
Section: Introductionmentioning
confidence: 55%
“…In fact, it has been proven that PK20 reduced influx of inflammatory cells into bronchoalveolar lavage fluid (BALF) and lungs, limited expression of nuclear transcription factor NF‐κB and concentration of pro‐inflammatory cytokines, malondialdehyde (MDA), secretory phospholipase A 2 (sPLA 2 ) and mouse mast cell protease (MCPT 1) in lung tissue, as well as the level of albumin in BALF. In the same experimental conditions, the beneficial inhibitory impact of PK20 was revealed on airway hyperreactivity (AHR) in response to methacholine provocation 16 …”
Section: Introductionmentioning
confidence: 94%
“…However, NT reduced mouse MC protease and malondialdehyde in lung homogenates in a murine hapten-induced asthma model, and the NTR1 antagonist did not reverse the NT-mediated reduced mouse MC activation [ 134 ]. Moreover, NT-based chimeric peptide and endomorphin-2 also reduced the concentration of mouse MC protease in a similar model [ 135 ].…”
Section: Neuropeptide Regulation Of Mast Cellsmentioning
confidence: 99%